The effect of cold water immersion on the recovery of physical performance revisited: A systematic review with meta-analysis - Choo, H. C.; Lee, M.; Yeo, V.; Poon, W.; Ihsan, M. (Journal of Sports Sciences, 2022)
This review evaluated the effect of CWI on the temporal recovery profile of physical performance, accounting for environmental conditions and prior exercise modality. Sixty-eight studies met the inclusion criteria. Standardised mean differences were calculated for parameters assessed at <1, 1-6, 24, 48, 72 and =96 h post-immersion. CWI improved short-term recovery of endurance performance (p = 0.01, 1 h), but impaired sprint (p = 0.03, 1 h) and jump performance (p = 0.04, 6h). CWI improved longer-term recovery of jump performance (p < 0.01-0.02, 24 h and 96 h) and strength (p < 0.01, 24 h), which coincided with decreased creatine kinase (p < 0.01-0.04, 24-72 h), improved muscle soreness (p < 0.01-0.02, 1-72 h) and perceived recovery (p < 0.01, 72 h). CWI improved the recovery of endurance performance following exercise in warm (p < 0.01) and but not in temperate conditions (p = 0.06). CWI improved strength recovery following endurance exercise performed at cool-to-temperate conditions (p = 0.04) and enhanced recovery of sprint performance following resistance exercise (p = 0.04). CWI seems to benefit the acute recovery of endurance performance, and longer-term recovery of muscle strength and power, coinciding with changes in muscle damage markers. This, however, depends on the nature of the preceding exercise.